2018
DOI: 10.3389/fneur.2018.00967
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence and Familial Inheritance of Intronic NIPBL Pathogenic Variant Associated With Mild CdLS

Abstract: Splicing pathogenic variants account for a notable fraction of NIPBL alterations underlying Cornelia de Lange syndrome but are likely underrepresented, due to overlooking of non-canonical intronic variants by traditional and contemporary sequencing methods. We describe five subjects, belonging to three families, displaying a mild Cornelia de Lange syndrome phenotype who carry the NIPBL pathogenic variant c.5329–15A>G, affecting the IVS27 branch site, yet reported in a single case. By RNA analysis we evidenced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Splice variants appear to occur more often in patients with a more severe phenotype (22). Nonetheless, few family cases with splice variants and mild phenotype have been reported (23). However, based on our data, such variants in a mosaic stage can also be detected in CdLS patients with a mild phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Splice variants appear to occur more often in patients with a more severe phenotype (22). Nonetheless, few family cases with splice variants and mild phenotype have been reported (23). However, based on our data, such variants in a mosaic stage can also be detected in CdLS patients with a mild phenotype.…”
Section: Discussionmentioning
confidence: 99%
“… Comparison of typical facial features of ( A ) Wiedemann–Steiner syndrome [ 26 ]; ( B ) Coffin–Siris syndrome; ( C ) Kabuki syndrome; ( D ) Cornelia De Lange syndrome [ 27 ]; ( E ) Rubinstein–Taybi syndrome [ 28 ]. …”
Section: Figurementioning
confidence: 99%
“…This approach could be especially relevant regarding CdLS. In this disorder, although a number of familial cases have been reported ( Gillis et al, 2004 ; Krantz et al, 2004 ; Slavin et al, 2012 ), only exceptionally, the presence of the causative variant could be confirmed in blood-derived DNA of the parents ( Niu et al, 2006 ; Deardorff et al, 2007 ; Slavin et al, 2012 ; Krawczynska et al, 2018 ; Masciadri et al, 2018 ). The reason could fairly lie either in the lack of sensitiveness of the detection method or in the presence of the variant strictly in some germinal cells.…”
Section: Introductionmentioning
confidence: 96%